Défense de la langue et développement des territoires : l'aragonais et ses promotrices/promoteurs - Carmen Alén Garabato (Lengas)
This article focuses on the efforts that contemporary activists are making to ensure that this language, Aragonese, does not disappear. In the first part, it is a question of some glottopolitical acts promoted from below, with particular attention to the role played by women. In the second part, we propose a brief sociolinguistic analysis of the institutional policy carried out from above, in particular from 2015 to 2023. The objective is to show the originality and the dynamic heritage process of some of these actions.These analyzes are based on several field surveys carried out in several small towns in northern Aragon (Ansó/Ansón, Echo/Hecho, Benás/Benasque, Graus) and in Zaragoza between 2018 and 2022, as part of a project of Occitanie-Aragon cross-border cooperation funded by the Occitanie Region (2018-2023).